Do electoral systems affect how citizens hold their government accountable? Evidence from Africa. Issue 3 (3rd April 2021) - Lockwood, Sarah J.; Krönke, Matthias
ABSTRACT: A large body of literature suggests that electoral system type has an impact on voting behaviour, but little work has been done looking at its effects on other forms of democratic accountability, such as contacting elected representatives and protesting. Using data from 36 African countries, we find that the type of electoral system has a significant relationship with these other forms of participation. Citizens in PR systems are significantly more likely to protest than those in majoritarian ones, while those in majoritarian systems are more likely to contact elected representatives. We argue that this is because the connection between citizens and representatives in majoritarian systems is clearer, closer, and more responsive, making contact an effective strategy and providing an efficient "safety valve" when citizens want to hold their government accountable. The lack of a similar connection in most PR systems, in contrast, leads citizens to turn to protest more regularly.